Research Progress in Peripheral Nerve Regeneration and Repair - Dai Xudong (BIO Web of Conferences)
Peripheral nerve injuries frequently result in sensory and motor dysfunction, significantly impacting patients' quality of life. Consequently, promoting regeneration and functional recovery following such injuries has become a primary focus of clinical research. Currently, autologous nerve transplantation is considered the gold standard for the treatment of peripheral nerve defects. However, this approach presents several limitations, including a scarcity of donor tissues, the potential formation of painful neuromas, and damage to the donor site. This article reviews recent advancements in the field of peripheral nerve regeneration and repair, aiming to provide valuable insights for the clinical management of peripheral nerve injuries.